REPETITION SPEED INFLUENCE ON INCREASING TENDENCY FOR HEART RATE IN WEIGHT TRAINING - Remus VĂIDĂHĂZAN; Iacob HANȚIU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2017)
The benefits of weight training are consequences of the workout. A weight training program is a composite of several variables that can be combined in a multitude of options to achieve the desired effects (Ratamess, 2012). Identifying these variables and their correct planning is essential to anticipate a beneficial purpose of weight training program (American College of Sports Medicine, 2007). Our research took place between February 9 and April 19, 2015, in the gym of the Faculty of Physical Education and Sports of the Babeș-Bolyai University of Cluj-Napoca. The research objective was to analyse the trend of increase in heart rate (HR) at different speeds of execution for repetitions of the weight training exercises. The results obtained suggest that the tempo of execution influence the increasing tendency for heart rate in weight training. In general, we noticed that as the speed of execution decreases the growing trend of HR is lower. But those conditions apply only at specific speed of execution for repetitions and they are influenced by the specific of muscle involved in exercise.